Covid Vaccine: Is It the “Holy Grail” For Dental Profession? - Rashmi Paramashivaih; Rathana. M; Prabhuji. MLV; ShaeestaKhaleelahmed Bhavikatti (Journal of Orofacial Research, 2021)
Objectives: The present survey attempts to assess the 1. Efficacy of both Covishield & Covaxin in protection against covid infection. 2. The time intervals between 1st and 2nd dose and duration after the 2nd dose of vaccine in protection against covid infection. 3. Role of protective measures post-vaccination. 4.General awareness about covid vaccine among dental professionals. Methodology: This cross-sectional study was conducted among dental professionals across India. An online structured questionnaire was created using Google Forms application and was sent to the dental professionals through WhatsApp mobile application. The questionnaire was administered between the months of March 2021 – April 2021 and was sent to 250 dentists from various parts of the country. Data were compiled and subjected to statistical analysis. Results: The questionnaire was sent to 250 dental professionals. Out of 250, 124 (49.6%) participants took part in the survey. Majority of the dentists (89.8%) have completed both the 1st & 2nd dose of vaccination. Though it cannot completely rule out their susceptibility to covid infection. Conclusion: Irrespective of the type of vaccine (Covishield/ Covaxin) more than 90% of the participants seemed to be protected against covid infection probably if there is adherence to the timing of both doses as well as the common infection control measures are followed post-vaccination.